PERFORMANCE MOTIVATION OF TEACHERS AND LEADERSHIP OF SCHOOL ADMINISTRATORS AFFECTING EFFECTIVENESS FOR THE SCHOOLS UNDER THE OFFICE OF SECONDARY EDUCATIONAL SERVICE AREA 9 - กล้าหาญ, ปกรณ์วิท; รักงาม, ชัยพจน์; ชำนาญ, สมุทร (Academic Journal Phranakhon Rajabhat University, 2018)
The purposes of this research were to study motivation, relationship, factors in performance of teachers and leadership of administrators affecting to effectiveness for schools and to develop prediction equation for effectiveness of schools under the Office of Secondary Education Service Area 9. The sample used in this study were 338 teachers of 2016 academic year under the Office of Secondary Education Service Area 9 using stratified random sampling as size of school. The instrument used in data collection was 5 Levels Rating Scale with all of 3 sections, namely questionnaire for the opinion on performance motivation of teachers, leadership of school administrators and effectiveness for schools under the Office of Secondary Education Service Area 9 with discrimination being between 28-83, reliability being equal to .86, .87, .96 and .93 respectively. Computer program was used in data analysis. Statistics used in data analysis were mean (), standard deviation (SD), Pearson’s product moment correlation and Stepwise multiple regression analysis. Results of study found that: 1. The factors on the success in working, work attribute in performance, responsibility, recognition and performance motivation of teachers under the Office of Secondary Education Service Area 9 in overview and each aspect were at all much level. 2.The factors on the organization atmosphere of schools, performance motivation of teachers and leadership of administrators generally had statistically significantly positive relationship with school effectiveness under the Office of Secondary Education Service Area 9 at moderate and high levels of .01 3. The factors on the performance motivation of teachers and leadership of administrators affected statistically significantly positive aspect to schools under the Office of Secondary Education Service Area 9 at level of .01 4. Prediction equation for effectiveness of schools under the Office of Secondary Education Service Area 9 was 73.60 percent by writing as raw scores equation as follows: Y = .813 + .313X22 + .093X13 + .182X21 + .094X15 + .131X11 Z= .408X22 + .099X13 + .216X21 + .140X15 + .128X11